Designing a Business Development Strategy Using a Business Model Canvas in the Nickel Mining Industry (Case Study of PT. Indrabakti Mustika, Southeast Sulawesi) - Ari, Yufri; Harianto, Eric; Christian, Timotius Febry (Jurnal Locus Penelitian dan Pengabdian, 2025)
The nickel mining industry plays a crucial role in Indonesia’s economy, particularly in Southeast Sulawesi, which holds one of the largest nickel reserves in the country. PT. Indrabakti Mustika is one of the key mining companies operating in this region. However, the company faces significant challenges, including commodity price fluctuations, intense global competition, and increasing sustainability demands. This study aims to design a business development strategy using the Business Model Canvas (BMC) framework to enhance the company’s competitiveness and sustainability. A descriptive qualitative method with triangulation was employed, involving interviews, questionnaires, and documentation. The research informants included five internal company representatives, one customer, and one benchmarking informant from the Southeast Sulawesi Provincial Department of Energy and Mineral Resources (ESDM). Data were collected through in-depth interviews, field observations, and document analysis. The results indicate that the BMC framework effectively maps the company’s business model, identifies development opportunities, and formulates appropriate strategies. Strategic recommendations include product diversification, operational efficiency, market expansion, sustainability initiatives, and research collaboration, with a strong emphasis on aligning with industry trends such as downstream processing and environmental sustainability. Implementation is advised to be adaptive and data-driven.